APLIKASI INFORMASI FASILITAS PELAYANAN KESEHATAN BERBASIS ANDROID DI WILAYAH KABUPATEN BANGKA - Nur Risqinawati; Yang Agita Rindri; Sari Mubaroh (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Information on existing health service facilities in Bangka Regency is still inadequate due to the absence of an information system or application that provides information about existing health service facilities in Bangka Regency. Therefore, a means of disseminating information is needed to make it easier for the public to obtain information about the location and available health care facilities. So that in this study an Android-based application was designed which aims to provide location information and health service facilities. In this study, data collection was carried out by taking data from every service facility in Bangka district. This application is made using the waterfall method or waterfall diagram. The literature study that supports the design of this application development uses UML. While the software used to build this application is Android Studio 4.22. The results of this study are expected to assist the community in providing information about locations, routes that can be passed, and health services found in each health service unit.